Predictability of the quasi‐biennial oscillation and its northern winter teleconnection on seasonal to decadal timescales. Issue 5 (7th March 2014) - Scaife, Adam A.; Athanassiadou, Maria; Andrews, Martin; Arribas, Alberto; Baldwin, Mark; Dunstone, Nick; Knight, Jeff; MacLachlan, Craig; Manzini, Elisa; Müller, Wolfgang A.; Pohlmann, Holger; Smith, Doug; et al.
Abstract The predictability of the quasi‐biennial oscillation (QBO) is examined in initialized climate forecasts extending out to lead times of years. We use initialized retrospective predictions made with coupled ocean‐atmosphere climate models that have an internally generated QBO. We demonstrate predictability of the QBO extending more than 3 years into the future, well beyond timescales normally associated with internal atmospheric processes. Correlation scores with observational analyses exceed 0.7 at a lead time of 12 months. We also examine the variation of predictability with season and QBO phase and find that skill is lowest in winter. An assessment of perfect predictability suggests that higher skill may be achievable through improved initialization and climate modeling of the QBO, although this may depend on the realism of gravity wave source parameterizations in the models. Finally, we show that skilful prediction of the QBO itself does not guarantee predictability of the extratropical winter teleconnection that is important for surface winter climate prediction.